Gestión operativa y su incidencia en los procesos de recaudaciones de la jefatura de mercados del gad municipal del Cantón el Empalme, año 2023. - Triviño Parrales, Natali Eloisa (2025)
The main objective of this research, entitled "Operational Management and its Impact on the Collection Processes of the Market Headquarters of the Municipal GAD of El Empalme Canton, Year 2023," was to evaluate how operational management influences the collection processes of said headquarters during the year 2023. A qualitative-quantitative methodology was used, which allowed the problem to be addressed through the application of inductive, deductive, historical-logical, and descriptive methods. To this end, data was collected and interpreted through direct observation, interviews, surveys, and analysis of relevant documentation, highlighting internal procedures related to collection. The study population included 322 people. 89.60% of merchants indicated that lack of financial resources is the main reason for non-timely rent payments; 8.09% expressed dissatisfaction, and 2.31% mentioned forgetfulness. Likewise, a lack of initiative to assume the political risk associated with the closure of establishments and the initiation of enforcement proceedings was identified. It was concluded that the current state of municipal markets, in relation to compliance with operational management for the recovery of overdue loans, is precarious due to insufficient resources on the part of merchants, especially in the formalization of lease contracts.